2001
DOI: 10.1002/1099-0682(200107)2001:7<1807::aid-ejic1807>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

New MnII Complexes with an N/O Coordination Sphere from TripodalN-Centered Ligands − Characterization from Solid State to Solution and Reaction with Superoxide in Non-Aqueous and Aqueous Media

Abstract: The crystal structure of a dimeric bis(µ-carboxylato)Mn II Mn II complex (2) with a tetradentate N-centered tripodal ligand, N,N-bis [(1-methylimidazol-2-yl)methyl]glycinate, is presented. The carboxylates are bridging monodentate. This complex shows some striking differences to the previously published parent compound 1 obtained with the closely related ligand N- [(1-methylimidazol-2-yl)methyl]-N-(2-pyridylmethyl)glycinate. The carboxylato bridges in both structures are shown to be disrupted in solution. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 79 publications
5
48
1
2
Order By: Relevance
“…Moreover, the IC 50 values calculated for 1 and 2 were higher than the values calculated for Mn(ClO 4 ) 2 Á6H 2 O [26]. It is clear from the electrochemical data that the Mn II /Mn III redox couples are not in the proper range for 1 and 2 and hence some other mechanism similar to that of SOD activity of Mn(ClO 4 ) 2 Á6H 2 O could be involved for the scavenging of superoxide ions [26,27]. The DNA binding properties of complexes were studied by UVvisible, circular dichroism and fluorescence spectroscopy.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Moreover, the IC 50 values calculated for 1 and 2 were higher than the values calculated for Mn(ClO 4 ) 2 Á6H 2 O [26]. It is clear from the electrochemical data that the Mn II /Mn III redox couples are not in the proper range for 1 and 2 and hence some other mechanism similar to that of SOD activity of Mn(ClO 4 ) 2 Á6H 2 O could be involved for the scavenging of superoxide ions [26,27]. The DNA binding properties of complexes were studied by UVvisible, circular dichroism and fluorescence spectroscopy.…”
contrasting
confidence: 55%
“…The inhibition study for 1 and 2 gave rise to a curve similar to the curve found by Biencenue et al [25] and the curve did not go beyond 65-70% inhibition. Moreover, the IC 50 values calculated for 1 and 2 were higher than the values calculated for Mn(ClO 4 ) 2 Á6H 2 O [26]. It is clear from the electrochemical data that the Mn II /Mn III redox couples are not in the proper range for 1 and 2 and hence some other mechanism similar to that of SOD activity of Mn(ClO 4 ) 2 Á6H 2 O could be involved for the scavenging of superoxide ions [26,27].…”
mentioning
confidence: 72%
“…Several reports [20,60,[65][66][67][68][69][70][71] are there by which one can select a manganese complex that could mimic SOD activity considering the electrochemical properties. Our electrochemical data showed the Mn(II)/Mn(III) couple, responsible for the catalytic activity, was within the proper range [60,69].…”
Section: Redox Properties and Sod Activitymentioning
confidence: 99%
“…Mn complexes containing carboxylato ligands are of interest, because of their intriguing structures [1][2][3][4][5][6][7][8][9][10][11][12][13] and potential applications in catalysis etc. [7][8][9][10][11]; e.g., some 'highly efficient Mn catalase mimics' with dinuclear Mn structures were reported recently [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11]; e.g., some 'highly efficient Mn catalase mimics' with dinuclear Mn structures were reported recently [12,13].…”
Section: Introductionmentioning
confidence: 99%